Physicochemical Quality of Spent Broiler Breeder Hen Chicken Koftas Added with Different Levels of Raw Banana Dried Powder - Sharada, M V Sneha; Indumathi, J; Reddy, G V Bhaskar; Shakila, S; Mouli, A Chandra (Journal of Meat Science, 2023)
The present study was undertaken to evaluate the effect of different levels of raw banana dried powder on the quality characteristics of chicken koftas. The raw banana dried powder was incorporated at three different levels viz. 2, 4 and 6% in the formulation. The products were analyzed for various physicochemical and sensory attributes. pH, emulsion stability, cooking yield, water holding capacity, moisture, crude fibre and total ash content of the products showed significant (P
Keywords: Chicken koftas; Raw banana dried powder; Physico-chemical parameters; Sensory analysis